Maternal and perinatal outcomes of delivery after a previous Cesarean section in Enugu, Southeast Nigeria: a prospective observational study - Ugwu GO; Iyoke CA; Onah HE; Egwuatu VE; Ezugwu FO (Dove Medical Press, 2014)
George O Ugwu,1 Chukwuemeka A Iyoke,1 Hyacinth E Onah,1 Vincent E Egwuatu,2 Frank O Ezugwu2 1Department of Obstetrics and Gynaecology, University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla, Enugu, Nigeria; 2Department of Obstetrics and Gynaecology, Enugu State University Teaching Hospital (ESUTH), Parklane, Enugu, Nigeria Background: Obstetricians in developing countries appear generally reluctant to conduct vaginal delivery in women with a previous Cesarean because of lack of adequate facilities for optimal fetomaternal monitoring. Objective: To describe delivery outcomes among women with one previous Cesarean section at a tertiary hospital in Southeast Nigeria. Methods: This was a prospective observational study to determine maternal and perinatal outcomes of attempted vaginal birth after Cesarean sections (VBAC) following one previous Cesarean section. Analysis was done with SPSS statistical software version 17.0 for Windows using descriptive and inferential statistics at 95% level of confidence. Results: Two thousand six hundred and ten women delivered in the center during the study period, of whom 395 had one previous Cesarean section. A total of 370 women with one previous Cesarean section had nonrecurrent indications, of whom 355 consenting pregnant women with one previous Cesarean section were studied. A majority of the women (320/355, 90.1%) preferred to have vaginal delivery despite the one previous Cesarean section. However, only approximately 54% (190/355) were found suitable for trial of VBAC, out of whom 50% (95/190 had successful VBAC. Ninety-five women (50.0%) had failed attempt at VBAC and were delivered by emergency Cesarean section while 35 women (9.8%) had emergency Cesarean section for other obstetric indications (apart from failed VBAC). There was no case of uterine rupture or neonatal and maternal deaths recorded in any group. Apgar scores of less than 7 in the first minute were significantly more frequent amongst women who had vaginal delivery when compared to those who had elective repeat Cesarean section (P=0.03). Conclusion: Most women who had one previous Cesarean delivery chose to undergo trial of VBAC, although only about half were considered suitable for VBAC. The maternal and fetal outcomes of trial of VBAC in selected women with one previous Cesarean delivery for nonrecurrent indications were good. Obstetricians in this area should do more to allow VBAC in women with one previous Cesarean section for nonrecurrent indications. Keywords: previous Cesarean section, vaginal birth, pregnancy, VBAC